ISU-ISU PENDIDIKAN LUAR SEKOLAH (KELUARGA DAN MASYARAKAT): DEFINISI, TANTANGAN, DAN SOLUSI - Sukari; Fityatul Muharromah; Asmira Efendi (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Out-of-school education (OECD) is an integral part of the national education system, encompassing non-formal and informal education within families and communities. This study aims to examine the role, challenges, and strategic solutions of OECD in supporting formal education, particularly in the digital era and post-pandemic. Through a literature review of various recent studies, it was found that OECD makes a significant contribution to character building, equitable access to education, and life skills development. However, OECD still faces several challenges such as socioeconomic disparities, low digital literacy, minimal parental involvement, fragmentation of community-based programs, and the significant impact of the COVID-19 pandemic on access to and quality of learning. This study recommends strengthening collaboration between schools, families, and communities, improving digital literacy, and integrating community programs to strengthen the role of OECD in realizing inclusive and sustainable education.